Pengaruh Upah Minimum, Pendidikan, Literasi Digital, dan Lapangan Kerja Informal terhadap Tingkat Pengangguran Terbuka (Tpt) di Pulau Jawa Tahun 2015-2022 - Putri, Jeany Sukma; Priyono, Rakhmat (Lingka Ekonomika, 2025)
Java has the highest labour force in Indonesia, which contributes to an elevated open unemployment rate due to the imbalance between job seekers and available vacancies. Previous studies have shown that factors such as the Provincial Minimum Wage (UMP), education level, digital literacy, and informal employment may influence unemployment. Despite being the nation’s economic hub, Java records the highest open unemployment rate in Indonesia. This study aimed to examine the effects of the Provincial Minimum Wage, education level, digital literacy, and informal employment on the open unemployment rate in six provinces in Java from 2015 to 2022. A quantitative approach was applied using secondary data and the Fixed Effect Model for panel data analysis. The findings show that the Provincial Minimum Wage does not significantly affect the open unemployment rate. In contrast, higher education levels, improved digital literacy, and greater availability of informal employment significantly reduce unemployment. These results suggest that policymakers should focus on enhancing workforce skills through training, expanding access to education, and supporting informal sectors such as micro, small, and medium enterprises to create broader employment opportunities.